POLA ASUH SINGLE PARENT (STUDI KASUS SINGLE PARENT (IBU) BEKERJA DI KELURAHAN SIDOMULYO TIMUR KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU) - Novi Zuriati; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to identify single parent and obstacle parenting The impediment to incitement in the flow of the sidomulyo timur marpoyan damai pekanbaru city care system conducted by single parent is shown by how to give attention, apreciation and motivation, and discipline and self-discipline. To get results from research, researchers use qualitative research methods and use purposive sampling technique by extracting data through observation, interview, and documentation. Research shows parenting which is applied by single mothers in the household sidomulyo timur marpoyan damai pekanbaru city peace leads to democratic and permissiv. Democratic parenting pattern is more applied by 4 single mother then 1 single mother with a parenting pattern permissive. Hindrance obstacle in doing parenting are economic status and pressure as single parent Keywords: Single Mother, Parenting